2012
DOI: 10.1093/ndt/gfs328
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure variability and outcomes in chronic kidney disease

Abstract: Current findings suggest that SBPV may be of use for risk stratification in CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 28 publications
1
64
1
1
Order By: Relevance
“…To calculate VVV of BP, we used data from seven followup visits that occurred 6,9,12,16,20,24, and 28 months after randomization. We started at the 6-month follow-up visit to avoid potential confounding by BP changes that occurred between randomization and that visit (mean BP fell by approximately 8/5 mmHg).…”
Section: Study Visits Bp Measurements and Calculation Of Vvv Of Bpmentioning
confidence: 99%
See 1 more Smart Citation
“…To calculate VVV of BP, we used data from seven followup visits that occurred 6,9,12,16,20,24, and 28 months after randomization. We started at the 6-month follow-up visit to avoid potential confounding by BP changes that occurred between randomization and that visit (mean BP fell by approximately 8/5 mmHg).…”
Section: Study Visits Bp Measurements and Calculation Of Vvv Of Bpmentioning
confidence: 99%
“…In some but not all studies, persons with higher BP variability had more rapid CKD progression as measured by declines in eGFR or increases in urinary albumin (9)(10)(11)(12)(13). Some studies of persons with diabetes have shown an association of BP variability with more clinically impactful renal outcomes, including ESRD (10,14), but such an association has not been shown among persons without diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Formally considered "noise," greater degrees of systolic BP visitto-visit variability (SBV) may be associated with an increased incidence of stroke and overall mortality in several cohort studies (1)(2)(3)(4). In a Northern European cohort, for example, individuals in the top decile of SBV had a 3.25-fold higher risk of subsequent stroke compared with those in the lowest decile (1).…”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal retrospective, observational, and multicentre study has found an association between systolic BPV, defined as the ratio of the SD to the mean systolic BP of five values recorded during 4-5 months, and the risk of death but not of progression to dialysis in 374 elderly subjects with chronic renal failure [56]. In addition, Yokota et al demonstrated that SD and CV of office systolic BP measured at 12 consecutive visits were significantly associated with deterioration of renal function in patients with nondiabetic chronic kidney disease [57].…”
Section: Impact Of Long-term Bpv On Target Organ Damage and Cardiovasmentioning
confidence: 99%